Optimization of Silver Nanoparticle Biosynthesis with Papaya (Carica Papaya L) Seed Ethanol Extract and its Evaluation on Antibacterial Effects - Rahma, Alifa Noora; Suratno, Suratno (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
The utilization of papaya plants (Carica papaya L) heretofore is focusing on their aril/mesocarp, leaves, and flowers, while the seeds are still neglected. Thus, this recent study attempts to make use of papaya seeds as a green-synthesis bioreductor of silver nanoparticles. It aims at finding out the characteristics of silver nanoparticles of ethanol extract of papaya seeds (AgNPs-EEPS), investigating the optimization as well as the characteristics of the AgNPs-EEPS anti-acne cream formula, and examining the antibacterial activity of Propionibacterium acnes on the AgNPs-EEPS anti-acne cream. The software design expert with factorial design method was applied to optimize the AgNPs-EEPS biosynthesis and cream formula. The analysis of the formation of AgNPs-EEPS characteristics, employing various levels of temperature and extract concentration, and applying UV- VIS spectrophotometry, resulted in a wavelength of 415 nm. Meanwhile, the implementation of particle size distribution testing, using PSD on the optimum concentration by 6% with temperature 65°C, generated a wavelength of 54 nm, pI 0.820, and zeta potential -7,7 mV. The optimization of the AgNPs-EEPS cream formula obtained optimum results at a stearic acid level 7 and cetyl alcohol 6. The characteristics of the cream produced a cream that was physically stable and met the requirements of good topical preparation. The anti-acne cream from silver nanoparticles ethanol extract of papaya seeds has the antibacterial activity of Propionibacterium acnes which belongs to the moderate category.